TECHNOLOGY FOR DEVELOPING CREATIVITY AND AESTHETIC TASTE IN PRESCHOOL CHILDREN THROUGH THE USE OF NATURAL MATERIALS - Abrorova Dildora Anvar qizi (International Journal of Literature and Language Studies, 2026)
This article scientifically analyzes the pedagogical foundations, modern technologies, and practical significance of developing creativity and aesthetic taste in preschool children through the use of natural materials. The study demonstrates that the use of natural materials broadens children's imagination, enhances their creative thinking, aesthetic perception, fine motor skills, and ecological awareness. Furthermore, the structural components of an innovative pedagogical technology based on the use of natural materials in preschool educational institutions were developed. The research findings indicate that the systematic use of natural materials contributes to the development of independent thinking, artistic taste, a responsible attitude toward nature, and creative competencies in preschool children.